Remarks on some adaptive ecological trends of Pelobates cultripes from Portugal: thermal requirement, rate of development and water regulation - Cei, José Miguel Alfredo María (1971)
Spawning, tadpole biology, rate of development, tolerance to water loss and water absorption, of Pelobates cultripes from Portugal, were studied, having in mind similar researchs carried out on western American spadefoots.